Laparoscopic Orthotopic Kidney Transplantation in Swine: A Novel Vascular Prop Device for Venous Anastomoses - Zhang, Peng; Han, Xiu-wu; Zhang, Xin; Zhu, Xu-hui; Li, Tao; Li, Yan-sheng; Chen, Yuan-hao; Li, Gao; Han, Long-xi; Zhang, Rong-jie (Frontiers in Surgery, 2021)
Objective: To investigate the safety and efficacy of a vascular prop device for laparoscopic orthotopic kidney transplantation (LOKT) in swine. Material and Methods: Twenty swine were randomly divided into two groups. A vascular prop device was used in the observation (VP) group, and the vein beltization technique was used in the control (VB) group. The right kidney, as a donor graft, was laparoscopically transplanted to the location of the left kidney after a left nephrectomy. Data on the operative time, venous anastomotic time, vein stenosis, etc., and the survival of the swine in the two groups were recorded. Results: The mean transplant operative time, the mean cold ischemia time, and the venous anastomotic times in the VP group were significantly shorter than those in the VB group. Seven swine in the VP group and three swine in the VB group survived for 7 days. Autopsy results showed the occurrence of one artery stenosis and one vein stenosis in the VP group and one artery stenosis and five vein stenoses in the VB group. The median survival time was 6.25 days for the swine in the VP group and 4.40 days for those in the VB group. Conclusions: The vascular prop device is safe and feasible for LOKT in swine and may accelerate venous anastomosis and ensure the quality of venous anastomotic stoma.